School-to-work transitions under unequal conditions : a regionalised perspective on the ‘discouraged worker’ hypothesis - Weßling, Katarina [Verfasser]; Andreas Hartung [Verfasser]; Hillmert, Steffen [Verfasser] (My University, 2023)
„Against the background of considerable regional disparities, we test the “discouraged worker” hypothesis, which postulates that poor regional socioeconomic conditions foster students’ aspirations for more education, ultimately leading to an extension of their educational careers. Our two dependent variables are (i) whether students aspire to prolong their general school careers or enter vocational training and (ii) whether they in fact prolong their school careers. To that end, we link regional-level data to individual-level data from the German National Educational Panel Study (NEPS). To describe regional conditions adequately, we illustrate geographical patterns in socioeconomic conditions relevant for school-to-work transitions (e.g., labour market conditions and availability of vocational training opportunities). We compare two operationalisations of regional areas: (i) administrative districts and (ii) public transport areas. Our results show that students are more likely to aspire to prolong their general school careers in socioeconomically deprived regions. Moreover, the effects are stronger when school-based vocational training opportunities are scarce. The effects on actual transitions vary according to the school track attended and the availability of educational alternatives in the general school system. Finally, the operationalisation of regions varies regarding effect sizes and corresponding levels of statistical significance.“ (authors‘ abstract; BIBB-Doku)
Keywords: G 1.3.2.2 Übergänge; G 2.1.4 Regionalisierung; G 1.3.2 Bildungsverhalten und -verläufe; L 5 Beratung & Orientierung; 370; Berufseinmündung; Regionale Disparität; Einflussfaktor; Bildungsaspirationen; Bildungsverhalten; Bildungsentscheidung; Nationales Bildungspanel